2023
DOI: 10.3389/fpsyg.2022.976102
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant customers’ food leftover reduction intention derived from nature connection and biospheric values: A comparison between men and women

Abstract: As the COVID-19 pandemic extends over a long period of time, the World Food Programme (WFP) estimated that food insecurity would take place in the near future. Previous studies focused on various kinds of interventions for food waste prevention. Surprisingly, however, research tackling consumer attitudes and behaviors as a way to reduce food waste is still rare. To fill this gap in the literature, this study examined the antecedent roles of restaurant customers’ nature connection and biospheric values in foste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…HNC and biospheric orientation in our study were apparently strongly related, but in other studies, these two individual characteristics are often considered separately and, in parallel, affect pro‐environmental behaviour. For example, in a recent study on restaurant customers' intention to reduce food leftovers, Kim et al (2023) demonstrated that HNC and biospheric orientation had a significant positive influence on environmental self‐identity and intentions for pro‐environmental behaviour. Interestingly, there was also an interaction between the two constructs (HNC and biospheric values) moderated by gender; the HNC of male customers increased their biospheric values more strongly than in the case of female customers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HNC and biospheric orientation in our study were apparently strongly related, but in other studies, these two individual characteristics are often considered separately and, in parallel, affect pro‐environmental behaviour. For example, in a recent study on restaurant customers' intention to reduce food leftovers, Kim et al (2023) demonstrated that HNC and biospheric orientation had a significant positive influence on environmental self‐identity and intentions for pro‐environmental behaviour. Interestingly, there was also an interaction between the two constructs (HNC and biospheric values) moderated by gender; the HNC of male customers increased their biospheric values more strongly than in the case of female customers.…”
Section: Discussionmentioning
confidence: 99%
“…HNC and biospheric orientation in our study were apparently strongly related, but in other studies, these two individual characteristics are often considered separately and, in parallel, affect pro-environmental behaviour. For example, in a recent study on restaurant customers' intention to reduce food leftovers, Kim et al (2023) demonstrated that HNC and biospheric orientation had a significant positive influence on environmental self-identity and intentions for pro-environmental behaviour.…”
Section: Common Factors Affecting Hncmentioning
confidence: 99%